Hungry bone syndrome like presentation following single-dose denosumab for hypercalcaemia secondary to sarcoidosis with IgA nephropathy. Issue 7 (8th July 2022) - Nachankar, Amit; Katyal, Amit; Bansal, Naresh; Bishnoi, Alka
Abstract : A woman in her mid-50s with IgA nephropathy, sarcoidosis and steroid-induced diabetes mellitus presented with generalised paraesthesia and spontaneous tetany. She had received denosumab 60 mg subcutaneously 8 weeks previously for parathyroid hormone independent hypercalcaemia. At admission, she had severe hypocalcaemia (5 mg/dL), hypophosphataemia (1.9 mg/dL), hypomagnesaemia (1.4 mg/dL) and elevated serum creatinine (1.48 mg/dL) with prolonged QTc (corrected QT interval) on electrocardiograph. She initially received intravenous calcium and magnesium followed by oral calcium carbonate and calcitriol. Her prednisolone dose was tapered to 5 mg/day. Evaluation showed secondary hyperparathyroidism (1474 pg/mL) and elevated 1, 25-dihydroxy vitamin D (195 pg/mL). After 1 week of oral calcium carbonate (3000 mg/day) and calcitriol (1.5 µg/day), she achieved normocalcaemia (8.1 mg/dL). To conclude, denosumab for hypercalcaemia with renal insufficiency causes prolonged severe symptomatic hypocalcaemia and hypophosphataemia mimicking hungry bone syndrome. It is important to periodically monitor for hypocalcaemia after denosumab.